The impact of adjuvant oxaliplatin and tumor sidedness on the overall survival of stage IIB colon cancer patients: A multicentre study - ARIKAN, RUKİYE (My University, 2023)
The aim of this multicentre retrospective study was to compare the efficacy of adjuvant chemotherapy regimens both with and without oxaliplatin and tumor sidedness in stage IIB (pT4aN0) colon cancer patients. This study included patients with stage IIB colon cancer who underwent curative surgery and received adjuvant chemotherapy. The patients were divided into two groups (one with and one without oxaliplatin) to compare the overall survival (OS) in right- and left-sided tumors. The study population included 298 patients with stage IIB colon cancer (median age: 57) of whom 69.1% were male. Forty-four per cent of these patients (n = 131) were diagnosed with right-sided colon cancer. The median follow-up duration was 35.9 months. In the entire population, a median OS was not reached, and the five-year OS was 83%. The median disease-free survival (DFS) was 12 months. There was no significant difference in terms of the five-year OS between right- (82%) and left-sided (84%) colon tumors (p = 0.67). In addition, the five-year OS of patients treated with and without oxaliplatin were 76% and 89%, respectively, and there was no statistically significant difference (p = 0.23). The five-year OS of the patients treated with and without oxaliplatin were 83% and 96.5%, respectively, (p = 0.8) in right-sided colon tumors, while it was 75% and 93% (p = 0.06), respectively, in left-sided colon tumors. Tumor sidedness and the addition of oxaliplatin to adjuvant chemotherapy were not found to be associated with the OS in stage IIB colon cancer patients in our study. Further large prospective studies that also include MSI, RAS and BRAF status data are warranted in colon cancer patients.
Keywords: Tıp; Temel Eczacılık Bilimleri; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyokimya; Dahili Tıp Bilimleri; İç Hastalıkları; Onkoloji; Cerrahi Tıp Bilimleri; Patoloji; Eczacılık; Yaşam Bilimleri; Temel Bilimler; Medicine; Basic Pharmaceutics Sciences; Health Sciences; Fundamental Medical Sciences; Biochemistry; Internal Medicine Sciences; Internal Diseases; Oncology; Surgery Medicine Sciences; Pathology; Pharmacology and Therapeutics; Life Sciences; Natural Sciences; ONKOLOJİ; Klinik Tıp; Klinik Tıp (MED); BULAŞICI HASTALIKLAR; İmmünoloji; Yaşam Bilimleri (LIFE); PATOLOJİ; Biyoloji ve Biyokimya; FARMAKOLOJİ VE ECZACILIK; Farmakoloji ve Toksikoloji; ONCOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); INFECTIOUS DISEASES; IMMUNOLOGY; Life Sciences (LIFE); PATHOLOGY; BIOLOGY & BIOCHEMISTRY; PHARMACOLOGY & PHARMACY; PHARMACOLOGY & TOXICOLOGY; General Immunology and Microbiology; Pharmacology; Immunology; General Pharmacology, Toxicology and Pharmaceutics; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); Histology; Pathology and Forensic Medicine; Pharmacology (medical); Biochemistry (medical); Pharmacy; Drug Guides; Infectious Diseases; Overal survival; colon cancer; stage IIB; oxaliplatin; FLUOROURACIL; CHEMOTHERAPY; THERAPY; LEUCOVORIN; GUIDELINES; PROGNOSIS; LOCATION; OUTCOMES; NUMBER; TRIAL; Overal survival; colon cancer; stage IIB; oxaliplatin